Analysis of interrelations of psychophysiological and physiological indicators of martial arts athletes - Romanenko, V.; Iermakov, S.; Podrigalo, L.; Rovnaya, O.; Sotnikova-Meleshkina, Z.; Goloha, V.; Ruban, L. (Baltic Journal of Health and Physical Activity, 2019)
The article presents a comparative analysis of interrelations of psychophysiological and physiological indicators of martial art athletes while performing functional tests. Material and methods: 63 martial art athletes were divided into groups: the 1st group - 34 athletes of "striking" martial arts (taekwondo ITF, WTF, karate, hand-to-hand fight), age (17.58±0.08) years; the 2nd group - 18 Greco-Roman and freestyle wrestlers, age (18.94±0.33) years; the 3rd group - 11 judo and sambo athletes, age (18.73±0.23) years. Participants performed a test to define the choice reaction time with parallel control of the heart rate for 3 minutes. Results: Indicators of the 1st and the 3rd groups did not significantly differ. Relevant excess of specific weight of significant and confident correlations was found in the 2nd group. The synchronization labilization indicator in the 2nd group was twice as high as in the 1st and the 3rd groups. The mean correlation coefficient in all groups belonged to the average interval. The indicator values of system formation in the 2nd group were significantly higher than in the other groups. Conclusions: Wrestlers are characterized by a higher degree of adaptation tension opportunities in comparison with other athletes.